Big ideas to safeguard food in a changing climate - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
View the Big Ideas for addressing climate change in agriculture. For more visit the Ideas Marketplace at http://www.agricultureday.org Filmed Live at Agriculture, Landscapes and Livelihoods Day 5, 3 December 2012 in Doha, Qatar.